L2 motivational self system : a case of Thai EFL senior high school students - Rosukhon Swatevacharkul (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study explored the ideal L2 self, ought-to L2 self, and L2 learning experience of the L2 motivational self system (L2MSS) among Thai EFL senior high school students. It took the form of an explanatory mixed-methods research design using the L2MSS questionnaire adopted from Taguchi et al. (2009) and Subekti (2018) to collect quantitative data from 183 students and a semi-structured interview with 6 students for qualitative data. Results from the questionnaire revealed that the ideal L2 self and L2 learning experience were high, while the ought-to L2 self was moderate. The thematic content analysis generated five themes: 1) use of English in the envisioning future career, 2) entertainment as a motivator for self-study, 3) influence of external motivational factors on internal motivation, 4) the impact of learning context, and 5) threat of examination on learning for communication. The paper concludes by recommending further research on a relationship of L2MSS constructs and English learning achievement and how the three motivation constructs predict English learning achievement. Researching the roles of parents in creating English learning motivation, and peers influence on self-efficacy development as a means to generate self-images is also suggested.